2013
DOI: 10.1016/j.jocn.2012.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of positive syphilis serology and meningovascular neurosyphilis in patients admitted with stroke and TIA from a culturally diverse population (2005–09)

Abstract: The study aims were to determine the prevalence of positive syphilis serology and meningovascular neurosyphilis (NS) in patients admitted with transient ischaemic attack (TIA) and stroke to a tertiary hospital serving a culturally diverse community. A retrospective cohort analysis was conducted using routinely collected administrative data and medical records to identify patients admitted with TIA, stroke and other conditions, with positive syphilis serology, between 2005 and 2009. Direct medical record review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 17 publications
1
25
2
1
Order By: Relevance
“…Syphilis and especially meningovascular neurosyphilis is a well-recognized cause of stroke in young patients. 21 Our results should be interpreted with caution, because no additional diagnostic tests for (neuro)syphilis were performed, including nontreponemal tests or cerebrospinal fluid examination. Still, our data suggest that syphilis testing should be considered part of the work-up of stroke in SSA.…”
Section: Discussionmentioning
confidence: 80%
“…Syphilis and especially meningovascular neurosyphilis is a well-recognized cause of stroke in young patients. 21 Our results should be interpreted with caution, because no additional diagnostic tests for (neuro)syphilis were performed, including nontreponemal tests or cerebrospinal fluid examination. Still, our data suggest that syphilis testing should be considered part of the work-up of stroke in SSA.…”
Section: Discussionmentioning
confidence: 80%
“…Around a quarter of patients with MVS have prodromal symptoms, likely due to concomitant meningitis—intermittent headaches, vertigo, insomnia or behavioural changes 5 8 11. These may occur for days,11 weeks or even months prior to the ischaemic event 5. The presentation of the ischaemic event itself depends on the vascular territory involved—most commonly the MCA 4 5 11.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the most likely manifestations include contralateral hemiplegia, hemianaesthesia, homonymous hemianopia and aphasia 8. Less common locations for the arteritides are the basilar8 or anterior spinal arteries 11…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, false positives can occur with bloodcontaminated CSF. 15 Australia is currently experiencing two distinct syphilis epidemics, among urban men who have sex with men and in heterosexual Aboriginal people in regional and remote areas, predominantly across the Top End. When serological tests are negative, a presumptive diagnosis of neurosyphilis can be made on the basis on an elevated CSF protein or monocytic pleocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…14 A retrospective Australian study found that syphilis serology was requested in only 27% of patients presenting with stroke, of which 4% were positive. 15 Australia is currently experiencing two distinct syphilis epidemics, among urban men who have sex with men and in heterosexual Aboriginal people in regional and remote areas, predominantly across the Top End. 16 Given the ongoing prevalence of syphilis, and its treatable nature, neurosyphilis needs to be recognised as a rare but important cause of stroke.…”
Section: Brief Communicationsmentioning
confidence: 99%